Clinical risk factors and periventricular leucomalacia. Issue 1 (January 1988) - Trounce, J Q; Shaw, D E; Levene, M I; Rutter, N
Abstract : Two hundred infants of below 1501 g at birth were regularly examined with real time ultrasound using a 7.5 MHz transducer. Abnormalities were categorized as periventricular haemorrhage (PVH) (n = 107) or periventricular leucomalacia (PVL), with or without PVH (n = 52). Of the group with PVL, 25 had the appearances of prolonged flare without cavitation. Prospective assessments of up to 50 potential clinical risk factors were made wherever possible on each infant including stratification of all blood gas and systolic blood pressure data. Multivariate logistic regression analyses confirmed a strong correlation between immaturity and PVH but this was not found in cases of PVL. Independent variables associated with PVL included pneumothorax, maximum bilirubin concentration, surgery, and the proportion of time the infant's PaCO2 remained above 7 kPa. There was a very strong inverse correlation between anaemia and PVL. Systolic blood pressure data were carefully analysed and there was no relation between either hypotension or antepartum haemorrhage and the development of PVL.